Redesain Redesain Perumahan Transmigrasi Lokal Suku Asmat dan Mappi di Tepian Sungai Maro Merauke - Atiza Nurhuzna Atiza Nurhuzna; Muchlis Alahudin Muchlis Alahudin (Journal of Scientech Research and Development, 2022)
The Asmat and Mappi tribes are indigenous Papuan tribes that have inhabited the outskirts of the Maro river since the 1970s. These two tribes were accommodated by the Merauke district government at the start of the local transmigration program from the interior to the city of Merauke. The local transmigration housing, which has been inhabited for decades, in fact, has several problems, namely, the lack of fulfillment of settlement-scale housing infrastructure requirements and the very close distance between housing and the outskirts of the Maro river which is a waterfront area. This study aims to analyze the local transmigration housing area of the Asmat and Mappi tribes on the banks of the Maro river and further produce a new design in the form of Redesign. This type of research is descriptive qualitative with inductive analysis. Data collection method with direct obseravation, interviews/ interviews, literature studies and documentation on 50 local transmigration houses consisting of 30 Asmat tribal transmigration houses and 20 Mappi tribal transmigration houses located in Kelapa Lima village, Merauke District. The results of the analysis recommend a Redesign Result in the form of a Stilt House that is livable and safe from tidal flooding due to the rise of the Maro river water level.